THE CHARACTERISTICS OF SAGO FROND SAP FROM TWO SELECTED GROWTH STAGES; ANGKAT PUNGGUNG AND UPONG MUDA PALMS - Nurazureen Matnin; Awang Adeni, Dayang Salwani; Muhammad Norhelmi Ahmad; Nurashikin Suhaili (Malaysian Journal of Science, 2021)
Sago frond is produced in abundance upon harvesting of the sago palms for starch extraction, hence need to be utilized and developed into beneficial products. In this study, the sap which contains sugars and starch is obtained by roller crushing the skinned frond for use as fermentation medium. Fronds from different growth stages (namely Angkat punggung and Upong muda) and different positions within the rosette (inner and outer circle) of the sago palm were studied. Based on the results, the outer circle frond of Upong muda palm gave the highest volume of sap at 290mL/kg which equivalent to 1600 mL/frond. On top of that, sago frond sap has an acidic pH, with glucose as major sugar component and contained various kinds of minerals like calcium, potassium and manganese. All fronds from different growth stages contain glucose between 28-68 g/L and xylose 21-29 g/L, respectively. After 21 days of storage, it can be concluded that the amount of reducing sugars and starch in all samples obtained from different growth stages remained almost unchanged from the original. Subsequently after this study, both fresh and stored sago frond sap can be used as a fermentation substrate without any modification.